The Impact of IFRS Adoption and Corporate Governance Mechanisms on Audit Report Lag: Evidence from An Emerging Country - Souha Ben Gamra; Fadhila Hamza; Hela Borgi (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Purpose - The purpose of this paper is to investigate the impact of the International Financial Reporting Standards (IFRS) adoption and corporate governance mechanisms (e.g., Board characteristics and Audit Committee (AC) characteristics) on Audit Report Lag (ARL) in an emerging country, named Saudi Arabia. Methodology - We use a sample of 616 firm-year observations from the Tadawul Stock Exchange in Saudi Arabia for the period 2016-2019. Panel regressions were used. Findings - The results indicate that ARL has significantly increased after the IFRSs' adoption. This result may imply that IFRS adoption leads to a need of adaptation process. It may support the need for more training and IFRS education in Saudi Arabia. Additionally, both AC diligence and AC financial expertise significantly reduce ARL. It may support the Saudi regulatory requirement to equip audit committees with at least one member with accounting and financial expertise. However, the results show that AC size and Board characteristics (board size, board independence and board meetings) are not significantly associated with ARL. Contribution - Our study fills the gap in the existing literature by examining the impact of the IFRSs' adoption and the corporate governance characteristics on ARL, whose results remain mixed and rare in Saudi Arabia, an emerging and under-studied context.
Keywords: M40; M41; M42; M48; 650; Audit Report Lag; Corporate governance; Saudi Arabia; IFRS